A comparative study of the biosorption of lead(II) ions to Z. ramigera and R. arrhizus - Sa?, Y.; Özer, D.; Kutsal, T. (My University, 1995)
Parameters that affected adsorption rates of lead(II) ions on Z. ramigera and R. arrhizus were investigated. The adsorption rates and equilibrium metal removal were strongly affected by pH, temperature, and initial metal concentration. Both micro-organisms exhibited the highest lead-adsorptive rate at pH 4.5-5.0. Maximum adsorption rates of metal ions to Z. ramigera and R. arrhizus were obtained at temperatures ranging from 25 to 45°C. The initial adsorption rate of metal ion increased with increasing metal ion concentration for Z. ramigera and R. arrhizus up to 150-200 mg litre-1 and 200-300 mg litre-1, respectively. Isotherms for the adsorption of lead on Z. ramigera and R. arrhizus were developed and Freundlich constants determined from the Freundlich adsorption isotherms. © 1995.